Noninvasive Lipoma Size Reduction Using High‐Intensity Focused Ultrasound. Issue 10 (18th July 2013) - Shemer, Avner; Brawer, Solli; Amichi, Boaz; Azhari, Haim
<x xml:space="preserve">Abstract</x> Background Lipomas are common benign mesenchymal tumors commonly removed using excision, but in certain cases, surgery is undesirable or ineffective. High‐intensity focused ultrasound (HIFU) offers a noninvasive tumor ablation tool increasingly used in the clinic. Objective To evaluate the efficacy and safety of a noninvasive lipoma size reduction technology using HIFU. Materials & Methods Twelve lipomas in nine patients were treated. Patients underwent four treatment sessions with a 3‐week interval between treatments. Blood and urine tests and tolerability based on a standard visual analogue scale (VAS) were used to monitor patients for adverse effects. Lipoma volume was determined by measuring width and length (manually) and depth (ultrasonically). Results The range of lipoma size was 2.7–169.4 cm3 before treatment and 0.2–119.8 cm3 after treatment. Mean volume reduction was 58.1 ± 22.8%. When palpated, the lipomas felt much softer than before treatment. The average VAS score was 4.1 ± 2.4. No significant adverse effects were noted. Conclusion The treatment was shown to be effective in noninvasively reducing lipoma size. The average volume reduction was substantial and statistically significant. The treatment was safe and well‐tolerated. HIFU may be an alternative treatment modality in cases of lipoma.